Summing the parts: How does “bundling” affect willingness-to-pay for seeds and insurance in a sample of Kenyan farmers? - Kramer, Berber; Waweru, Carol; Malacarne, Jonathan G. (2023)
Agricultural households, particularly those operating in rainfed systems in low income countries, are vul nerable to a variety of climate and market risks that pose serious threats to their well-being. While more resourced households are able to pass much of this risk o↵ to financial markets, less resourced households often have few options to do the same. Instead, they are forced to rely on precautionary savings (Lee and Sawada, 2010), drawing down assets (Carter and Lybbert, 2012), or informal risk sharing, all of which have limited ability to deal with shocks (Carter and Maluccio, 2003). Despite the demonstrated impact of tools like agricultural insurance (Cai, 2016; Bertram-Huemmer and Kraehnert, 2015; Hill et al., 2019), such products are often not available in remote, resource poor areas or, when they are, face low demand due to inaccessibility, lack of information, or concerns about contract quality (Karlan et al., 2014; Clarke, 2016). A fuller understanding of household willingness-to-pay (WTP) for risk-reducing technologies, as well as how this valuation depends on both characteristics of the technology and of the adopting household, is an important step toward designing tools that are attractive and accessible to their target populations. In this paper, we study WTP for two risk-reducing technologies — agricultural insurance and stress tolerant seeds — as stand-alone products and as components of a bundle. Bundling a productivity enhancing technology with a risk reducing technology has been proposed as a way to mitigate the risk of agricultural investment to farmers, input suppliers, and financial institutions (Carter, Galarza and Boucher, 2007). Bundling of multiple risk reducing technologies has also been proposed as a way to increase coverage and reduce cost, thereby releasing precautionary savings for productive investment (Lybbert and Carter, 2015).